A influência da energiewende na política externa alemã - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work aims to analyze the influence of Energiewende on foreign policy German. For this, we assume that Energiewende provided greater insertion of Germany in the International System, acting as a player in renewable energy and influencing other countries, in particular the European Union, follow their course of energy transition through soft power. For this, we analyze the context of Energiewende in the German domestic context, where we understand that the promotion of renewables took place for safety and energy efficiency, both to end nuclear energy and to detach from dependence on Russian gas supplies. That said, we infer that Russian-German relations are strategic and pragmatic, given the construction of the Nord Stream 1 and 2 pipelines at the same time as Germany invests in renewables, increasing its participation in the energy network. Lastly, asserted the construction of authority and influence of Germany within the scope of the Union European — especially growing in the period of crises between Russia and Ukraine, in which she served as a mediator—where she acts as a leader and example in promoting the energy efficiency through renewable energy, which makes clear the instrumentalization of energy as a soft power tool in the region.
The influence of energiewende on German foreign policy
Keywords: Energiewende; Transição energética; Alemanha; Soft power; Energy transition; Germany; CNPQ::CIENCIAS SOCIAIS APLICADAS